Reading Fluency and Reading Motivation in Hebrew in Students with Reading Disabilities. Issue 2 (20th May 2021) - Vaknin‐Nusbaum, Vered; Nevo, Einat
Abstract: We examined the relationships of two aspects of reading motivation with reading fluency performance in 79 third‐ to sixth‐grade Hebrew‐speaking students with reading disabilities. Reading fluency tests were administered, in addition to a reading motivation questionnaire (MRP‐R), all of which examined students' self‐concept as readers, as well as the value they attach to reading. Correlations were found between students' self‐concept and their reading performance. Additionally, no differences were found between grade levels in reading motivation. Furthermore, word rate, accuracy, and reading self‐concept predicted text rate beyond grade level. Finally, significant differences were found in reading measures in favor of readers with a high self‐concept, suggesting that students with reading disabilities should not be perceived as a homogenous group.